1993
DOI: 10.2466/pr0.1993.73.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the One-Session Eye-Movement Desensitization Reprocessing Procedure for Eliminating Traumatic Memories

Abstract: Eye-movement Desensitization Reprocessing (EMDR) is a relatively new therapy technique originally reported to eliminate traumatic memories (rape, catastrophes) in one session. Early published research has tended to support the technique. However, there is controversy and at least one unpublished recent study by Rothbaum who reported only about one-half of her cases had successful outcomes. The present study was conducted as a preliminary evaluation in 1990. Our results were judged to be unsuccessful in five of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…There have been case reports or studies which have suggested that EMDR is not an effective treatment for PTSD (Jensen, 1994;Oswalt, Anderson, Hagstrom, & Berkowitz, 1993). These studies have been criticized (as an example, Jensen, 1994) for the use of psychology interns as experimenters, the use of disability-dependent military veterans, inadequate training in the procedure, and low fidelity to EMDR treatment protocols (Greenwald, 1996;Shapiro, 1996).…”
Section: Treatment Efficacymentioning
confidence: 99%
“…There have been case reports or studies which have suggested that EMDR is not an effective treatment for PTSD (Jensen, 1994;Oswalt, Anderson, Hagstrom, & Berkowitz, 1993). These studies have been criticized (as an example, Jensen, 1994) for the use of psychology interns as experimenters, the use of disability-dependent military veterans, inadequate training in the procedure, and low fidelity to EMDR treatment protocols (Greenwald, 1996;Shapiro, 1996).…”
Section: Treatment Efficacymentioning
confidence: 99%
“…Considerable interest has recently been generated by case reports of rapid improvements in post-trauma symptoms using eye-movements, in the procedure known as eye-movement desensitization-reprocessing (EMD-R; Kleinknecht & Morgan, 1992;Lipke & B o t h , 1992;McCann, 1992;Oswalt, Anderson, Hagstrom & Berkowitz, 1993;Page & Crino, 1993;Puk, 1991;Shapiro, 1989u, b;Spector & Huthwaite, 1993;Wolpe & Abrams, 1991). In the original form of this procedure, clients imagine the traumatic event together with associated thoughts and somatic reactions while they visually track the therapist's finger, which moves rapidly from side to side across the visual field.…”
mentioning
confidence: 99%
“…At level 1, qualitative reports and uncontrolled studies (i.e., without control group) have suggested that EMDR might have interesting therapeutic results (e.g., Marquis, 1991 ; Puk, 1991 ; Wolpe and Abrams, 1991 ; Lipke and Botkin, 1992 ; Oswalt et al, 1993 ; Pellicer, 1993 ; Forbes et al, 1994 ; Spates and Burnette, 1995 ).…”
Section: The Scientific Community Is Divided About Emdrmentioning
confidence: 99%